2015
DOI: 10.5455/jnbs.1429042179
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment and Implication of Olfactory Dysfunction in Neuropsychiatric Disorders of Childhood and Adulthood: A Review of Literature

Abstract: The sense of smell is currently arousing a great deal of interest in the neuroscience area. This distinct sense has some unusual features: that it is the only sensory system 1. Introduction "Smell is the orphaned sense; it has been forgotten by medicine" (Birnbaum, 2011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 91 publications
0
6
0
4
Order By: Relevance
“…Children with ADHD also show functional manifestations of sensory problems, particularly in sensory seeking, auditory filtering, and in sensitivity to tactile, auditory, visual, taste and olfactory stimuli [12] known to be involved in the neurobiology of ADHD [15,16]. Very few studies have investigated olfactory impairment in children with ADHD and results are not consistent.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Children with ADHD also show functional manifestations of sensory problems, particularly in sensory seeking, auditory filtering, and in sensitivity to tactile, auditory, visual, taste and olfactory stimuli [12] known to be involved in the neurobiology of ADHD [15,16]. Very few studies have investigated olfactory impairment in children with ADHD and results are not consistent.…”
Section: Introductionmentioning
confidence: 83%
“…They also found highly significant right nostril impairment among the children with ADHD. Granizadeh et al [15] reported that children with ADHD have Engrami l vol. 38 l januar-mart 2016. l br.…”
Section: Discussionmentioning
confidence: 99%
“…В подавляющем большинстве исследований обоняния у больных шизофренией говорится об уменьшении у них обонятельной чувствительности, которое авторы интерпретируют как генерализованный дефицит остроты обоняния, отражающий структурные аномалии в периферической обонятельной системе, или как нарушения регуляции внутриклеточных сигнальных путей цАМФ, изменение активности дофаминовых рецепторов [1,2,12].…”
Section: Discussionunclassified
“…Сибирский вестник психиатрии и наркологии. 2020; 2 (107): 5-13. https://doi.org/10.26617/1810-3111-2020-2(107)- [5][6][7][8][9][10][11][12][13] Нарушения обоняния у больных с параноидной формой шизофрении ¹Бигдай Е.В., ²Тумова М.А., ¹Безгачева Е.А., ²Янушко М.Г., ²Муслимова Л.М., ²Иванов М.В.…”
Section: клиническая психиатрияunclassified
See 1 more Smart Citation